Alfred the Great: a diagnosis - Nicholas Summerton (Journal of the Royal Society of Medicine, 2026)
Based on a re-analysis of the available evidence it seems likely that Alfred the Great suffered from a painful perianal swelling as a teenager termed, in Latin, ficus . After this problem had resolved he was then troubled by an intermittently painful abdominal condition that affected him for most of his adult life. Although it is tempting to equate Alfred`s condition to a specific modern-day gastrointestional or urological diagnosis – as opposed to appreciating the nature and significance of his pain – it is argued that such precision is spurious and contributes little to developing a deeper understanding of his activities and behaviours in addition to their historical impacts.